Monthly progress report of July of Brac University new campus development project - BUCG-ABC Joint Venture (BUCG-ABC JV) (Brac University, 2023)
This record consists of general correspondence regarding the monthly progress report of July of Brac University new campus development project of Brac University new campus development project .